Evaluation of Trace Elements of Individuals Exposed to Cement Dusts in Ekpoma and Its Environs - Kingsley Airhomwanbor; Emmanuel Omon; Lucky Omolumen; Ernest Asibor; Bright Omolumen; Kingsley Ighedo (AlQalam Journal of Medical and Applied Sciences, 2023)
Background and aim. Cement dust consists of toxic constituents, the heavy metals like nickel, cobalt, lead, chromium and pollutants hazardous to the biotic environment, with adverse impact for human, animal vegetation, health and ecosystem. This study was carried out to assess the Lead, Manganese and Copper levels of individuals exposed to cement dusts in Ekpoma and environs. Methods. A total of 100 samples were used in this study comprising fifty (50) cement factory workers and fifty (50) control subjects. Manganese, Copper and Lead concentrations were estimated using Atomic Absorption Spectrophotometer. Statistical analysis was done using one-way analysis of variance and the student’s t-test. Results. The results obtained showed that Manganese and Lead were significantly higher (p<0.05), while Copper was significantly lower in individuals exposed to cement dust compared with control group (p<0.05). There was no significant difference (p>0.05) in Lead, Copper and Manganese of individuals exposed to cement dust according to age. Lead increased significantly (p<0.05) with duration of work, while Copper and Manganese did not show any statistically significant difference (p>0.05). Conclusion. The finding of this study showed that exposure to cement dust caused significant increase in Pb, Cu and Mn in individuals exposed to cement dust which indicates a possible metal toxicity in the subjects studied and these may have negative impact on their health. There was a progressive increase in trace elements concentration with duration of exposure. These observations emphasize the need for adequate safety and precautionary measures among cement factory workers and in individuals exposed to cement dust.